Новый вид слизистых споровиков (Myxosporidia) - Слухай, В.В. (Вестник зоологии, 1967)
The author finds the spores of this parasite on gills of Carassius carassius from the lakes of the Seversky Donets basin in May 1962. This species was also found on the gills of Rutilus rutilus from the Seliger lake (R. E. Shulman), the Syamozero lake (S. S. Shul-man) and Verkhny Don (N. I. Krasilnikova). Spore size: length — 8.5-13 µ, width — 6.3. (rarely) — 12.5 µ; the length of polar capsule: bigger —3.8-5.6 µ. and smaller — 22-3.3 µ ; their diametres: bigger — 2.2-3.3 µ and smaller — 10.7-2.5 µ.